Associations of diabetes mellitus with primary open angle glaucoma and Alzheimer’s disease: a large cohort study in UK biobank - Shi, Yan; He, Xinyue; Liu, William; Hu, Junming; Qiu, Wei Qiao; Zhang, Xiaoling; Fan, Zhigang (Frontiers in Endocrinology, 2025)
BackgroundRecent studies suggest that the diabetes might be associated with higher risk for primary open angle glaucoma (POAG) and Alzheimer’s disease (AD). However, studies have not addressed the critical issue of confounding by indication, and associations have not been evaluated in a large cross-sectional study. We started this cross-sectional study included United Kingdom Biobank (UKBB) participants with complete data (2006-2010) for analysis to explore the associations between diabetes mellitus (DM) and POAG and AD by considering depression and diabetic retinopathy (DR) as intermediate factors.Methods28,112 diabetes patients and 471,869 controls without diabetes were included from UKBB. Data on diagnosis of glaucoma, diabetes, depression, Alzheimer’s disease, diabetic retinopathy, apolipoprotein E (APOE) E4 genotypes and data from ophthalmologic examinations were gathered. We further collect the prevalence of DM, DR, depression, POAG and AD, gender, APOE E4 genotypes, C-reactive protein (CRP) levels to analysis.ResultsDepression, AD, and POAG were more prevalent in participants with DM compared with non-DM participants, and if DM patients had DR, the prevalence of those comorbidities was even higher than those without DR (all p<0.05). DM, DR, AD, and POAG were more prevalent in participants with depression compared with non-depression participants. Specifically, if DM patients had depression, the prevalence of DR and AD were even higher than those without depression (all p<0.05). In addition, using age-adjusted multivariable general linear model (GLM), we found DM and depression were associated with a higher prevalence of POAG in females while DM and APOE E4 negative status were associated with a higher prevalence of POAG in males. In both genders, DM, APOE E4, and depression were all associated with higher prevalence of AD in both univariable and multivariable GLM adjusted by age (all p<0.05). DM and depression were all associated with higher CRP, while carrying APOE E4 was associated with lower CRP levels in both univariable and multivariable GLM (all p< 0.001) in all populations.ConclusionsDR and depression, as comorbidities related to blood-retinal barrier and blood-brain barrier impairment in patients with DM, may play pivotal roles in the development of POAG and AD among DM patients.